PENGARUH KONFLIK PERAN GANDA, KEBIJAKAN KEHIDUPAN KERJA DAN DUKUNGAN ORGANISASI TERHADAP KINERJA MELALUI STRES KERJA PADA TENAGA KERJA WANITA SEKTOR INDUSTRI DI KOTA BATAM - Hikmah Hikmah (OPTIMA, 2017)
Batam is an industrial city, where workers in Batam are from various islands in Indonesia and also manpower from abroad (expatriates) in which labor-power is occupying the major industries on the island of Batam. The industries that dominate in Batam of which type of manufacturing industry. Manufacturing industry is heavily dependent on the availability and resource needs, namely human resources, especially women. The purpose of this study was to evaluate the performance of the dual role of women (dual role) who worked on the manufacturing industry in Batam and further discusses the relationship between work-family conflict, family-work conflict, work-life policies, organizational support, to the performance. The study was conducted by collecting quantitative data through questionnaires distributed to 268 respondents. Data collected were analyzed using Statistical AMOS as software for Structural Equation Modeling. Research findings show that work-family conflict had a positive effect on work stress, family-work conflict had a positive effect on the stress of work, policy work life has a positive effect on job stress, organizational support has a positive effect on job stress, work stress has an influence significant negative on performance.